Casa-gente/ habitar memórias: uma construção poética - Chiodelli, Diana Letícia (2023)
This research deals with poetic investigations about the creation processes between houses, people and memories. From the houses experienced since my childhood, between Santa Catarina and Rio Grande do Sul, I observe, register, collect and build a body of images accessed by different technology tools such as audio, video and photography, in a path to poetically represent the connections between the places of these houses and the people who inhabit them. It is in this path between inhabiting and experiencing memories of these places that this research seeks to connect the houses and the people, with the objective of understanding how they build a research concept in contemporary art: the house-people. Poetically, it seeks to develop methods of creating and documenting memories to build images of what is invisible to the naked eye and different from traditional methods of photography. Invented houses are the place for this research that is described on a methodological basis between poetics and ethnography (Passeron and Hall Foster), and organized through the invention of a research-house that accommodates axis-houses, places through which artistic processes will be approached: house -tapera, moving house, memory house and root house. Through them, places and personas connected by important concepts of the research are presented: the body of memories through objects, the places of affection, the relations between dwelling and belonging, and the transformations in the landscapes that provoke the displacement of people between them. places. The structure of theoretical investigation within this research-house raises a dialogue between poetic writing as an artistic work and the presence of authors such as Bachelard, Michael de Certeau, Ecléia Bosi, Rosa Alba, seeking connection with artists who find in the different paths of the art of which this research is also born to guide their poetic processes: Heidi Bucher, Louise Bourgeois, Lygia Clark, Alexandre Sequeira, Helene Sacco. From a place displaced from the artistic axes of the state of Santa Catarina, this research also becomes a space for provocations around the debates on access to the production and circulation of art. In this way, this investigation builds debates in the field of contemporary art, proposing different relationships about inhabiting landscapes that are transformed from memory, land expropriation processes and urban planning in large centers.